The Mechanism of Lipopolysaccharide Escaping the Intestinal Barrier in Megalobrama amblycephala Fed a High-Fat Diet - Dai, Yong-Jun; Liu, Wen-Bin; Abasubong, Kenneth Prudence; Zhang, Ding-Dong; Li, Xiang-Fei; Xiao, Kang; Wang, Xi; Jiang, Guang-Zhen (Frontiers in Nutrition, 2022)
With the popularity of western food characterized by excessive fat and sugars, obesity has currently been a public health issue. Low-grade chronic inflammation accompanied by obesity increases the risk of multiple epidemics such as diabetes, cancer and cardiovascular diseases. Here, we show that feeding Megalobrama amblycephala with a high-fat diet (HFD) drives obesity-related chronic inflammation and the penetration of lipopolysaccharide (LPS). Interference with antibiotics inhibits the produce of LPS and this alleviates the sustained release of pro-inflammatory factors induced by HFD. LPS penetration is attributed to weakened intestinal mucus barrier after high-fat exposure. Mechanically, the consumption of HFD inhibits the secretion of mucin 2 (MUC2) due to the induction of endoplasmic reticulum stress mediated by the inositol-requiring enzyme 1 (IRE1) /X box-binding protein 1 (XBP1) pathway in goblet cells. Furthermore, excessive lipid exacerbates the leakage of LPS across the intestinal epithelial cell barrier via the transcellular pathway. Mechanically, lipid increases the internalization of LPS in intestinal epithelial cells depending on the activation of fatty acid translocase (FAT/CD36). These results demonstrate that HFD causes the penetration of LPS due to the weakened intestinal mucosal barrier and the assistance of CD36.